Extraction of Iron (Fe) From Fly Ash Using Citric Acid and Oxalic Acid as Lixiviant - Suwardiyanto; Waladatus Sholikhaha; Dyah Hayuning Tyasa; Yudi Aris Sulistiyo (Indonesian Chimica Letters, 2025)
Reduction of iron (Fe) content within fly ash has been conducted by solid-liquid extraction using oxalic acid and citric acid as lixiviant. Separation of iron compounds using magnet and acid treatment have been performed prior to the extraction to decrease the iron concentration within the fly ash. Iron within the fly ash was extracted in several pH condition and several Fe/lixiviant molar ratio to evaluate their effect on the extraction. The extraction performance was evaluated toward residual iron concentration in the fly ash and amount of fly ash after extraction process. Residual iron was determined by spectrometer Uv-Vis using o-phenanthroline whereas the amount of fly ash was determined gravimetrically. Extraction using citric acid at pH of 6 and molar ratio of 1 : 4 has highest iron removal from fly ash whereas the highest fly ash residual was obtained by extraction at pH of 7 molar ratio of 1 : 2. The highest performance of oxalic acid as iron lixiviant was obtained at pH of 6 and molar ratio of 1 : 6 and the highest fly ash residual at pH of 6 and molar ratio of 1 : 3.